Self-Confidence: How Does the Experimentation of the Course Review Horay Learning Models Impact It? (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study aims to examine the differences in the experimental application of the Course Review Horay learning model on students' self-confidence in the PAI (Islamic Religious Education) subject at SMAN 12 Bandar Lampung. The background of this research is based on the low level of students' self-confidence, which is attributed to the use of conventional teaching models. The research method employed is quantitative with a quasi-experimental design approach. The sampling technique used is simple random sampling, as it reduces the potential for human bias in selecting cases to be included in the sample. This method is considered fair because every member of the population has an equal chance of being selected. The research subjects consisted of two classes: one experimental class using the Course Review Horay learning model and one control class using the conventional teaching model. Data were collected using a non-test instrument in the form of a self-confidence questionnaire. Data analysis was conducted using the Independent Samples T-Test, which showed a significance value of 0.00 < 0.05. It can be concluded that the results of this study demonstrate that the Course Review Horay learning model significantly improves students' self-confidence compared to conventional teaching methods. This study provides an important contribution to the development of learning models, particularly in the PAI subject. The implementation of the cooperative Course Review Horay learning model by teachers can create an effective learning environment to enhance students' self-confidence.